Admissible vector fields and related diffusions on infinite-dimensional manifolds - Elworthy, K.D.; Zhi-Ming Ma (Український математичний журнал, 1997)
A variation on the notion of “admissibility” for vector fields on certain infinite-dimensional manifolds with measures on them is described. It leads to the construction of associated diffusions and Markov semigroups on these manifolds via Dirichlet forms. Some classes of concrete examples are given. Розглядається варіант поняття „допустимих" векторних полів на певних нескінченновимірних многовидах з мірами на них. Це приводить до конструкції асоційованих дифузій та марковських підгруп на цих миоговидах за допомогою форм Діріхле. Подані певні класи конкретних прикладів.